Research Advances on Experimental Biology of Woody Plants of A Tamaulipan Thorn Scrub, Northeastern Mexico and Research Needs - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez; Kumari, Aruna; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2016)
The present review makes a synthesis of various aspects of applied biology of more than 30 woody plant species of a Tamaulipan Thorn scrub, Northeastern Mexico. This deals with the biodiversity of leaf traits, leaf anatomy, plant characteristics, wood anatomy, wood density, phenology and few aspects of physiology and biochemistry viz., leaf pigments, leaf epicuticular wax, trees with high nutritional values, carbon fixation, nitrogen and protein contents. The results show a large variability of all the morpho-physiological traits of the woody species related to the co-existence and adaptation of the woody species in semiarid environments. Special emphasis has been given to discuss the role of various morpho-anatomical and ecophysiological traits for adaptation to xeric environments such leaf anatomical traits (leaf surface, leaf lamina, petiole, venation system) and wood anatomical traits and few ecophysiological traits suchas pigments, epicuticular wax, leaf nutrients, carbon fixation etc., which could be related to the adaptation of the species in xeric environment. Different woody species possess specific adaptive mechanisms in a forest ecosystem. This also suggests research needs and put forward few hypotheses for efficient management of forest system. No such inter-disciplinary studies are available on Tamaulipan Thorn scrub.